MODE OF DELIVERY IN THE SECOND PREGNANCY OF MOTHER WITH HIGH MYOPIA AND HISTORY OF SECTIO CESAREAN: A CASE REPORT - Dian Lestari Hidayah; Farida Fitriana; Andriyanti; Ivon Diah Wittiarika; Ratna Dwi Jayanti (Indonesian Midwifery and Health Sciences Journal, 2023)
Background: Pregnant women with a history of cesarean section have problems choosing the delivery method for their next pregnancy. Sometimes there are still other risk factors, one of which is high myopia, which adds to the problem of choosing an effective delivery method with the advantages and disadvantages of each. Continuity of care in midwifery is very important in providing patients insight, knowledge, and support to make decisions about appropriate and safe delivery methods. Case report: A 29-year-old woman G2P1A0 with high myopia (minus 8) and cesarean scar three years ago for indications of high myopia (minus 10). In this second pregnancy, the mother underwent another SC because of high myopia minus 8, and the mother has not had a retinal laser until the present. Patients receive referrals from a primary health center for antenatal care and preparation for delivery at referral health facilities with high-risk pregnancies. Mothers are faced with two choices: TOLAC (Trial Of Labor After Cesarean Delivery) and ERCD (Elective Repeat Cesarean Delivery). The mother was consulted by an eye specialist at the referral hospital. The condition of the eye’s retina is good from the results of an eye specialist examination. However, it is still necessary to do a retinal laser process as prophylaxis if the mother wants to have a vaginal delivery. In the end, cesarean delivery is the mother's choice. Conclusion: Pregnancies with high myopia and cesarean scars need to receive full support from midwives and families to carry out comprehensive COC care to improve the health of mothers and children by assisting mothers in selecting delivery methods that are effective and safe for both mother and baby.